2020
DOI: 10.1111/gbb.12652
|View full text |Cite
|
Sign up to set email alerts
|

Moderate prenatal alcohol exposure impairs cognitive control, but not attention, on a rodent touchscreen continuous performance task

Abstract: A common feature associated with fetal alcohol spectrum disorders is the inability to concentrate on a specific task while ignoring distractions. Human continuous performance tasks (CPT), measure vigilance and cognitive control simultaneously while these processes are traditionally measured separately in rodents. We recently established a touchscreen 5‐choice CPT (5C‐CPT) that measures vigilance and cognitive control simultaneously by incorporating both target and nontargets and showed it was sensitive to amph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
0
19
1
Order By: Relevance
“…We first showed that female mice had slower rates to acquire discrimination criterion versus males, although this was not different in PAE versus controls (Marquardt et al, 2014). More recently, we found that while PAE spared attention on a touchscreen 5‐choice Serial Reaction Time Task, PAE in general, and female PAE mice, in particular, had significantly increased false alarm responses to nontarget stimuli on the 5‐Choice Continuous Performance Task (Olguin et al, 2020). Across these studies, female animals consistently had elevated latencies both to respond to stimuli, and to retrieve reward, although these measures did not always reach significance.…”
Section: Discussionmentioning
confidence: 92%
“…We first showed that female mice had slower rates to acquire discrimination criterion versus males, although this was not different in PAE versus controls (Marquardt et al, 2014). More recently, we found that while PAE spared attention on a touchscreen 5‐choice Serial Reaction Time Task, PAE in general, and female PAE mice, in particular, had significantly increased false alarm responses to nontarget stimuli on the 5‐Choice Continuous Performance Task (Olguin et al, 2020). Across these studies, female animals consistently had elevated latencies both to respond to stimuli, and to retrieve reward, although these measures did not always reach significance.…”
Section: Discussionmentioning
confidence: 92%
“…The CatwalkXT system (Noldus) was used to analyze gait and fine motor coordination according to methods previously described 24 . Mice were placed at one end of a 1.3 m glass runway and allowed to walk across to the other end to reach a dark goal box.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the neuronal populations, a clear threshold could not be identified, but overlap between control and FAE values ceases at around 70 mg/dL BEC and 1.5 g EtOH/Kg/day. Although a specific threshold of FAE could not be determined, these data add to the growing evidence that low-to-moderate FAE results in compromised hippocampal functioning [ 47 , 48 ] affecting synaptic activity [ 47 ], connectivity [ 47 , 49 ], neurogenesis [ 50 ], and plasticity [ 51 , 52 ] with adverse learning and behavior [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 97%